2007
DOI: 10.7863/jum.2007.26.8.1031
|View full text |Cite
|
Sign up to set email alerts
|

Breast Sonography in Localizing the Cause of Nipple Discharge

Abstract: Sonography was found to be a valuable method for localizing intraductal abnormalities, especially papillomatous lesions, in patients with nipple discharge with no other clinical or radiologic findings. Preoperative sonographically guided wire localization can be used successfully instead of conventional methylene blue staining in cases with problems in cannulation of the discharging duct. Galactography remains the primary diagnostic method, especially in depicting malignant causes of nipple discharge, which ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
48
1
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(55 citation statements)
references
References 21 publications
5
48
1
1
Order By: Relevance
“…Furthermore, a recent study [22] reports that direct magnetic resonance imaging galactography may provide more diagnostic information than conventional GL in patients with PND, because it can show both ductal morphology and the extent of disease before surgery. Also, sonography is a valuable method for localizing intraductal abnormalities, especially papillomatous lesions, in patients with nipple discharge with no other clinical or radiologic findings [23]. However, the sonographic detection of DCIS is difficult.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a recent study [22] reports that direct magnetic resonance imaging galactography may provide more diagnostic information than conventional GL in patients with PND, because it can show both ductal morphology and the extent of disease before surgery. Also, sonography is a valuable method for localizing intraductal abnormalities, especially papillomatous lesions, in patients with nipple discharge with no other clinical or radiologic findings [23]. However, the sonographic detection of DCIS is difficult.…”
Section: Discussionmentioning
confidence: 99%
“…In these conditions ultrasound might be inferior to galactography and might therefore play a limited role for the detection of peripheral small intraductal masses without ductal dilatation. In ductectasia, however, ultrasound can demonstrate the underlying lesion and its relationship to the ductal system [49].…”
Section: Discussionmentioning
confidence: 99%
“…While MMG is considered the standard initial imaging examination and may reveal microcalcifications and other signs of malignancy, it rarely provides information about the etiology of ND (Rissanen et al, 2007citing Cabioglu et al, 2003Dillon et al, 2006;Funovics et al, 2003;Sardanelli et al, 1997;Tabar et al, 1983). In the study by Tabar et al (1983), only half of the patients who presented with ND and were diagnosed with breast cancer had an abnormal mammogram.…”
Section: Mammography (Mmg)mentioning
confidence: 96%
“…Berg & Gilbreath (2000) reported that US identified 45 of 48 (94%) invasive tumor foci and 7 of 16 (44%) foci of DCIS while only 9 of 64 (14%) malignant foci were detected by US. Rissanen et al (2007) reported that in 52 patients with unilateral nipple discharge, 80% of papillomatous lesions, 58% of other benign lesions, and 20% of malignant lesions were sonographically positive, and among the 6 cases in which duct dilatation was the only sonographic finding, 3 (50%) were malignant lesions and the other 3 (50%) were papillomas and other benign lesions. In a study of 55 patients with bloody ND, Nakahara et al (2003) reported that of all findings, only the hypoechoic masses with smooth margins (NPV = 90.9%) and hypoechoic masses with irregular margins (positive predictive value (PPV) = 85.7%) were statistically significant.…”
Section: Ultrasonography (Us)mentioning
confidence: 99%